Fournier’s Gangrene: Lessons Learned from Multimodal and Multidisciplinary Management of Perineal Necrotizing Fasciitis - Ioannidis, Orestis; Kitsikosta, Loukiani; Tatsis, Dimitris; Skandalos, Ioannis; Cheva, Aggeliki; Gkioti, Aikaterini; Varnalidis, Ioannis; Symeonidis, Savvas; Savvala, Natalia Antigoni; Parpoudi, Styliani; Paraskevas, George K.; Pramateftakis, Manousos George; et al. (Frontiers in Surgery, 2017)
Background: Fournier’s gangrene is a rapidly evolving necrotizing fasciitis of the perineum and the genital area, the scrotum as it most commonly affects man in the vast majority of cases. It is polymicrobial in origin, due to the synergistic action of anaerobes and aerobes and has a very high mortality. There are many predisposing factors including diabetes mellitus, alcoholism, immunosuppression, renal and hepatic disease. The prognosis of the disease depends on a lot of factors including but not limited to patient age, disease extent and comorbidities. Methods: The current retrospective study is presenting the experience of our general surgery department in the management of Fournier’s gangrene during the last 20 years. The clinical presentation and demographics of the patients were recorded. Also we recorded the laboratory data, the comorbidities, the etiology and microbiology and the therapeutic interventions performed and we calculated the various severity indexes. Patients were divided to survivors and non survivors and all the collected data were statistically analyzed in order to assess mortality factors using univariate and then multivariate analysis. Results: In our series we treated a total of 24 patients with a mean age 58.9 years including 20 males (83.4%) and 4 females (16.6%). In most patients a delay between disease onset and seeking of medical help was noted. Comorbidities were present in almost all patients (87.5%) All patients were submitted to extensive surgical debridements and received broad spectrum antibiotics until microbioligal culture results were received. Regarding all the collected data there was no statistically significant difference between survivors and non survivors except the presence of malignancy in non survivors (p=0.036) and the lower hemoglobin (p<0.001) and hematocrit (p=0.002) in non survivors. However, multivariate analysis didn’t reveal any predictor of mortality. Conclusion: In conclusion, early diagnosis, aggressive thorough surgical treatment and administration of the proper antibiotic treatment comprise the cornerstone for the outcome of this disease. In small populations like in the present study it is difficult to recognize any predictors of mortality and even the severity indexes which take into account a lot of data cannot predict mortality.